2016
DOI: 10.1128/aac.01198-16
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Cysteamine against the Cystic Fibrosis Pathogen Burkholderia cepacia Complex

Abstract: There are no wholly successful chemotherapeutic strategies against Burkholderia cepacia complex (BCC) colonization in cystic fibrosis (CF). We assessed the impact of cysteamine (Lynovex) in combination with standard-of-care CF antibiotics in vitro against BCC CF isolates by the concentration at which 100% of bacteria were killed (MIC100) and checkerboard assays under CLSI standard conditions. Cysteamine facilitated the aminoglycoside-, fluoroquinolone- and folate pathway inhibitor-mediated killing of BCC organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Cysteamine has direct antimicrobial properties against common CF pathogens with a range of minimal inhibitory concentrations (MIC) [ 19 , 20 ]. We sought to extend this finding using antibiotic-resistant clinical isolates of 4 common CF pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Cysteamine has direct antimicrobial properties against common CF pathogens with a range of minimal inhibitory concentrations (MIC) [ 19 , 20 ]. We sought to extend this finding using antibiotic-resistant clinical isolates of 4 common CF pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Cys also prevents the formation of, and disrupts already established, Pseudomonas aeruginosa and Enterococcus faecalis biofilms (45,48). NAC and Cys show antimicrobial activity against Gram-positive and Gram-negative pathogens, with MICs usually falling in the range of 500 to 5,000 g/ml (45,46,(49)(50)(51), although lower values have been reported for some bacteria (46,52). It is generally recognized that the mechanisms underlying the therapeutic and clinical applications of NAC (and Cys) are still unclear and, possibly, more complex than previously envisaged (53).…”
Section: Discussionmentioning
confidence: 99%
“…This molecule is already approved for other diseases and its safety profile is known since 1994 ( Gahl et al, 2007 ). Moreover, cysteamine showed antimicrobial activity against P. aeruginosa , so recently Fraser-Pitt et al (2016) showed its effect in combination with antimicrobial agents used for the treatment of Burkholderia . In particular, they found that cysteamine was able to enhance the antimicrobial activity of tobramycin (even reversing resistance/insensitivity in 17 out of 36 strains), ciprofloxacin (reversing resistance/insensitivity in 10 strains), trimethoprim-sulfamethoxazole, but not ceftazidime.…”
Section: Molecules In Clinical Use For Other Diseasesmentioning
confidence: 99%
“…In particular, they found that cysteamine was able to enhance the antimicrobial activity of tobramycin (even reversing resistance/insensitivity in 17 out of 36 strains), ciprofloxacin (reversing resistance/insensitivity in 10 strains), trimethoprim-sulfamethoxazole, but not ceftazidime. Furthermore, inhibition of bacterial biofilm was observed in presence of sub-inhibitory concentrations of cysteamine ( Fraser-Pitt et al, 2016 ).…”
Section: Molecules In Clinical Use For Other Diseasesmentioning
confidence: 99%